Rai14 is a novel interactor of Invariant chain that regulates macropinocytosis - Lobos Patorniti, Natacha; Zulkefli, Khalisah Liyana; McAdam, Martin E.; Vargas, Pablo; Bakke, Oddmund; Progida, Cinzia (Frontiers in Immunology, 2023)
Invariant chain (Ii, CD74) is a type II transmembrane glycoprotein that acts as a chaperone and facilitates folding and transport of MHC II chains. By assisting the assembly and subcellular targeting of MHC II complexes, Ii has a wide impact on the functions of antigen presenting cells such as antigen processing, endocytic maturation, signal transduction, cell migration and macropinocytosis. Ii is a multifunctional molecule that can alter endocytic traffic and has several interacting molecules. To understand more about Ii's function and to identify further Ii interactors, a yeast two-hybrid screening was performed. Retinoic Acid Induced 14 (Rai14) was detected as a putative interaction partner and the interaction was confirmed by co-immunoprecipitation. Rai14 is a poorly characterized protein, which is believed to have a role in actin cytoskeleton and membrane remodelling. In line with this, we found that Rai14 localizes to membrane ruffles where it forms macropinosomes. Depletion of Rai14 in antigen presenting cells delays MHC II internalization, affecting macropinocytic activity. Intriguingly, we demonstrated that, similar to Ii, Rai14 is a positive regulator of macropinocytosis and negative regulator of cell migration, two antagonistic processes in antigen presenting cells. This antagonism is known to depend on the interaction between myosin II and Ii. Here, we show that Rai14 also binds to myosin II, suggesting that Ii, myosin II and Rai14 work together to coordinate of macropinocytosis and cell motility.